2020
DOI: 10.3390/ijerph17103427
|View full text |Cite
|
Sign up to set email alerts
|

Objective and Perceived Neighborhood Greenness of Students Differ in Their Agreement in Home and Study Environments

Abstract: Research has reported the associations between objective or subjective neighborhood greenness and health, with low agreement between the greenness scores. College students are prone to poor health, and data are lacking on home and university environments. We studied the agreement between greenness parameters and the associations of objective greenness with health in different locations. Three hundred and seventy-seven college students were recruited, with a mean age of 24 years, in the city of Graz, Austria. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…Other studies focusing on university students found that perceived greenness, UGSs, or academic GSs help them reduce feelings of anxiety, depression, and uncertainty or, conversely, promote psychological rehabilitation and academic performance [34,72,87,[171][172][173][174][175][176][177][178][179][180][181][182]. This has become even more apparent following the COVID-19 pandemic lockdowns that were implemented on a global level.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies focusing on university students found that perceived greenness, UGSs, or academic GSs help them reduce feelings of anxiety, depression, and uncertainty or, conversely, promote psychological rehabilitation and academic performance [34,72,87,[171][172][173][174][175][176][177][178][179][180][181][182]. This has become even more apparent following the COVID-19 pandemic lockdowns that were implemented on a global level.…”
Section: Discussionmentioning
confidence: 99%
“…The main findings of all but one [19] of the studies pointed to a positive association between campus greenery and well-being of students, indicating the restorative role of greenness and water bodies on campus and/or around students' residential areas. One of the 32 studies, undertaken in a natural desert environment, found a protective role of brownness (35% decrease in the incidence of depression), which may be explained by scarce green areas and familiarity with the desert environment and color [29]. In 12 of the studies, authors focused on green spaces' settings and type of nature in association to mental wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Perceptions of greenness can be fluid based on differences in the makeup of the natural environment. For example, some previous work that suggests the environment in which a study is conducted may lead to more discordance than the measures used to assess perceived and objective greenness [ 65 ]. The different relationships between the subjective and objective greenness scales that arose when using the same scales in different environments may be due to the variations in the types of greenness across different environments, suggesting the attributes of the greenness are important in perceptions but may not be captured in all objective measures.…”
Section: Discussionmentioning
confidence: 99%